(untitled) (Research, Society and Development, 2020)
Objective: to know the perception of nurses about the application and purpose of clinical reasoning in the care of hospitalized adults with chronic diseases. Methodology: exploratory-descriptive study, with a qualitative approach. It was carried out with nurses working in adult inpatient units of a University Hospital in southern Brazil. Data collection took place from july to december 2018, through semi-structured interviews. The data were analyzed using the Thematic Content Analysis. Results: it was found that the nurses’ perception of clinical reasoning was applied (in)consciously in care and management activities. Its purpose was self-reported in the qualification of care, patient comfort and prevention of complications. Conclusion: these findings are believed to be guiding instruments for questioning, analysis, synthesis, interpretation, inference, inductive and deductive reasoning, intuition, application and creativity for nurses’ decision-making in care practices for adult hospitalized patients with chronic diseases.